Identifying past petroleum exploration related drill cutting releases and influences on the marine environment and benthic foraminiferal communities, Goliat Field, SW Barents Sea, Norway. Issue 2 (April 2018) - Aagaard-Sørensen, Steffen; Junttila, Juho; Dijkstra, Noortje
Abstract: The present multiproxy investigation of marine sediment cores aims at: 1) Identifying dispersion of petroleum exploration related drill cutting releases within the Goliat Field, Barents Sea in 2006/07 and 2) Assessing past and present influence of drill cuttings on the marine environment. The cores were recovered 5, 30, 60, 125 and 250 m from the drill site in the eastward downstream direction. Downstream dispersion of drill cuttings is evaluated by examining sediment grain size distribution and barium (Ba), heavy metal, total organic carbon and sulphur concentrations. Dispersion of drill cuttings was limited to < 125 m east from the drill site. Influence of drill cutting releases on the marine environment is assessed via microfaunal analysis of primarily calcareous benthic foraminifera. The findings suggest contemporaneous physical smothering at ≤ 30 m from the drill site, with a natural fauna reestablishing after drilling cessation indicating no long-term effect of drill cutting releases. Highlights: Assessment of environmental effect from marine drill cutting release in 2006/07. Fossil benthic foraminiferal faunas depict smothering effects. Live and fossil benthic foraminiferal faunas show post drilling faunal recovery. Fossil faunas allow establishment of in-situ reference conditions.